The role of human resources practices in conflict management: Implications for small-medium enterprises - (:unkn) unknown (IGI Global, 2013)
The aim of this chapter is to provide a conceptual basis on the role of HR (Human Resources) practices in conflict management in the context of small business. However, conflict management is not accounted as a formal function of HRM (Human Resources Management) such as selection, performance appraisal, or administrative services. Besides, HR functions in Small-Medium Entreprises (SMEs) are usually carried by owners or line managers while some practices might be outsourced, as well. Consequently, managing human resources is different in SMEs due to firm size, priorities of the owner, and informality. Therefore, the challenge is to build the link between HR functions and conflict management in the context of small business. In this respect, the chapter emphasizes the importance of managing human capital effectively in terms of managing conflicts. © 2014 by IGI Global. All rights reserved.